(untitled) (Fiep Bulletin - online, 2012)
The application of tests for functional evaluation of high-performance athletes is focused on cardiorespiratory fitness. It is proposed, to describe the cardiorespiratory and metabolic performance of athletes in cardiopulmonary exercise test, by the Bruce Protocol, comparing physiological responses, considering the characteristics of the sport practiced. The methodology consisted of an analytical cross-sectional descriptive study, with quantitative methodological design, in which twelve athletes from different athletics modalities were evaluated in 2008, six of them were males. The athletes were evaluated by anthropometric assessment, focusing on data for body mass index and fat percentage, and cardiopulmonary exercise test, by the Bruce Protocol on treadmill, evaluating cardiorespiratory performance from the oxygen volume consumption (VO2), carbon dioxide (VCO2), respiratory quotient (RQ), blood lactate (BL), heart rate (HR) and blood pressure (BP). The results showed that athletes with predominantly aerobic training had higher values of VO2 maximum (54.80±7.00) when compared with athletes of speed / explosion (41.81±7.00), which it was also found in RQ. Moreover, in aerobic training athletes, there was the realization of a greater number of stages in the stress test and lower lactate concentration, when compared with speed training athletes. From the analyzed results it can be concluded that athletes that practice predominantly aerobic modalities showed higher values of VO2 and remained in the aerobic range (RQ<1) at later stages, indicating an improved cardiorespiratory fitness. The results showed the effects of training on the efficient use of metabolic routes, characteristics of physical activities that promote physiological and metabolic adaptations, increasing physical capacity and optimizing the cardiorespiratory responses.